Study of the Causes and Magnitude of Wastage of Materials on Construction Sites in Jordan. (29th October 2014) - Bekr, Ghanim A.
Abstract : The research aims to study the causes and magnitude of wastage of construction materials on construction projects sites in Jordan. To achieve the research aim, the researcher had prepared a questionnaire form included questions about the causes of wastage and the estimated percentages of wastage of ten most popular kinds of materials used on construction sites in Jordan. Prior to the final formulation of the questionnaire form, a pilot survey was conducted. The form was revised in accordance with the feedback received. The number of causes adopted was 60 distributed on the six major categories. The form was distributed to 240 participants (clients, contractors, and consultants). The study revealed that the most important causes of wastage of materials on construction sites in Jordan are frequent design and client's changes; rework due to workers mistakes; poor contract documents; wrong and lack of storage of materials; poor strategy for waste minimization; shortage and lack of experience of skilled workers; poor site conditions; damage during transportation; theft and vandalism; and mistakes in quantity surveying and over allowance. In addition the study concluded that the percentage of wastage materials is accounted for by values between 15% and 21% on Jordanian construction sites.